A COMMUNICATION MANAGEMENT IN OVERCOMING REVENUE UNCERTAINTY IN THE APPLICATION OF THE WEIGHBRIDGE VINA SYSTEM AT PT. BGR LOGISTICS INDONESIA PALEMBANG BRANCH - Nur Syafitri; Badaruddin Azarkasyi (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
The role of communication management in developing the company and how the company can overcome the problems that exist in the company's organization. This study aims to determine communication management in overcoming income uncertainty in the application of the Weighbridge Vina system at PT BGR Logistics Indonesia Palembang branch. As for companies that are specialized in digital-based logistics, which of course have an extensive network, integrated, competitive, reliable and trustworthy solutions, this is the vision of the company PT BGR logistics Indonesia which certainly has a plan through strong communication management. PT BGR Logistics Indonesia in communication management overcomes income uncertainty through the implementation of communication management functions in its implementation, including planning, organizing, directing, and controlling, in which the goals of communication management can work. overcome the uncertainty of income that occurs in the Vina weighbridge application system. The research method used is descriptive qualitative research method, researchers find the object of the problem by reading various information, documentation or pictures, then thinking and seeing, then analyzing the activities of people around them and conducting interviews. The results show that the application of communication management at PT BGR Logistics Indonesia Palembang branch includes planning, organizing, directing, and controlling in overcoming the problem of income uncertainty and can be resolved properly with the role of management. communication, and can find factors that affect the problems that occur such as miss-communication, busyness and piles of work that makes it unfocused in directing subordinates, obstacles in the Vina system application when recording double errors, incorrect input or typing caused by blackouts, shift change of weighbridge operator which is a change of focus in the system. Through the obstacles that were learned, then the strengthening of communication management gave results as a form of solving the problem of the difference in income between the Vina system application and SAP or Operational Recap. Through the 4 functions of communication management, which means that it states that the implementation and role of communication management in a company is very important, especially in the company PT BGR Logistics Indonesia Palembang branch, and continues to make communication management a tool to seek problem solving and direct company activities in order to realize goals in order to improve the quality of the company in any sector.